ADAB GURU DAN MURID MENURUT IMAM NAWAWI ad-dimsyaqi - FUADI, SALIS IRVAN; KUSUMO, SUTRI CAHYO (AL-QALAM: JURNAL KEPENDIDIKAN, 2019)
This study aims to determine the etiquette of teachers and students according to Imam Nawawi in the book Al-Tibyān Fī ādābi Ḥamalah Al-Qur’ān and Al-Majmū ’Syarḥ Al- Al-Muhażżab. The results of this study are expected to be used to perfect the concept of the existing teachers and students in the world of education. This type of research is a library (library research). In collecting data, researchers get it from two sources, namely primary and secondary sources. This research is analytical descriptive, that is, research that describes what is an idea in the book Al-Tibyān Fī ādābi Ḥamalah Al-Qur’ān and Al-Majmū ’Syarḥ Al-Al-Muhażżab by Imam Nawawi. While the method of analysis in this study is content analysis, namely research in the form of in-depth discussion of the contents of a written information. The results of this study reveal that the teacher's etiquette is divided into four parts, namely the teacher's etiquette to himself, the teacher's etiquette to science, the etiquette of the teacher to students and teaching as well as the teacher's etiquette when teaching. Whereas students 'etiquette is divided into three, namely students' etiquette towards themselves, students 'etiquette towards teachers and knowledge and students' etiquette within the science assembly. From this description, clearly illustrated the manners of teachers and students relevant to Islamic religious education. The relevance of teachers and students to Islamic religious education there are four core areas, namely the relevance of the objectives of Islamic religious education, the relevance of educators and students as well as the relevance of Islamic religious education methods